Dynamic Strength and Fracture Behavior of Dual Phase Steel Under High Strain - M R, Sunilkumar; Schmidová, Eva; Hojka, Přemysl (TANGER, spol. s r.o., 2019)
Dual phase steel has been significantly used in the automotive industry for the outer body parts. It has high strength, good formability and high toughness. Passive safety during a crash is significant, which drives this experimental work. In this research work, dynamic strength and fracture behaviour of the dual phase steel DP500xxx under varying high strain rate has been investigated using pendulum hammer impact testing machine and Electrohydraulic testing machines. The Strain rate sensitivity of the steel and microstructural phase changes are studied at higher strain rates. Thin sheets of dual phase steel are tested with from quasi-static strain rate up to 103 s-1. Fracture mechanism is observed after the impact-tensile tests and strain hardening effect is measured using local hardness measurement. Measurement of local hardness gives the spread of the plastic deformation and nature of strain hardening.
Dynamická pevnost a lomové chování dvojfázové oceli
Keywords: dual-phase steel; dvoufázová ocel; citlivost na rychlost deformace; dynamická pevnost; lomové chování; strain rate sensitivity; dynamic strength; fracture behaviour